Respuesta :

(2^2)x(-1^2)-(-3^2)x(2+(-1)) =

(2^2)x(-1^2)-(-3^2)x(1)=

(4)x(1)-(9)x(1)=

4-9= -5


The value of the expression x²z² - y²(x + z) at x = 2, y = –3, and z = –1 will be negative 5. Then the correct option is B.

What is the value of the expression?

When the relevant factors and natural laws of a mathematical model are given values, the outcome of the calculation it describes is the expression's outcome.

The expression is given below.

⇒ x²z² - y²(x + z)

Substitute the value of the variable x = 2, y = –3, and z = –1. Then the value of the expression will be

⇒ (2)²(-1)² - (-3)²(2 - 1)

Simplify the expression, then we have

⇒ 4 × 1 - 9 × 1

⇒ 4 - 9

⇒ 5

Thus, the value of the expression x²z² - y²(x + z) at x = 2, y = –3, and z = –1 will be negative 5.

Then the correct option is B.

More about the value of expression link is given below.

https://brainly.com/question/23671908

#SPJ2